Evaluation of Lettuce Cultivars for Production on Muck Soils in Southern Florida - German Sandoya; Huangjun Lu (EDIS, 2020)
Lettuce as a commercial crop is planted mainly in organic soils ("muck") in the Everglades Agricultural Area (EAA) in south Florida. This updated publication of the UF/IFAS Horticultural Sciences Department presents a summary of previous cultivar releases by UF/IFAS as well as a description of cultivars currently planted in the EAA. Written by German Sandoya and Huangjun Lu. https://edis.ifas.ufl.edu/hs1225